Severe Gastritis after Administration of Nivolumab and Ipilimumab - Yoshito Nishimura; Miho Yasuda; Kazuki Ocho; Masaya Iwamuro; Osamu Yamasaki; Takehiro Tanaka; Fumio Otsuka (Case Reports in Oncology, 2018)
Immune checkpoint inhibitors such as ipilimumab, a cytotoxic T-lymphocyte-associated antigen-4 inhibitor, have been widely used for advanced malignancies. As these inhibitors improve antitumor immunity via T-cell modulation, immune-mediated adverse events associated with T-cell activation, such as colitis, might occur. Herein, we describe a 75-year-old Japanese woman with metastatic malignant melanoma who developed hemorrhagic gastritis after ipilimumab treatment. There was no macroscopic or clinical improvement of gastritis after proton pump inhibitor treatment. However, her condition improved after approximately 3 weeks of corticosteroid therapy and Helicobacter pylori eradication. This case suggests a potential association between severe gastritis and immune checkpoint inhibitor treatment. Although several reports have mentioned ipilimumab-associated colitis, gastritis is considered to be rare. In the present case, H. pylori-associated gastritis might have been exacerbated by the T-cell modulation effect of ipilimumab. To date, no report has clarified the mechanism by which ipilimumab modifies H. pylori infection. The present treatment course provides a helpful perspective for similar cases.